KEPEMIMPINAN INOVATIF DALAM IMPLEMENTASI KEBIJAKAN STRATEGIS PEMERINTAH KOTA MAKASSAR - Ramli, Muhammad (JPP (Jurnal Politik Profetik), 2017)
This article is aimed at seeking and analyzing the application of innovative leadership in the implementation of urban strategic policy of the City of Makassar such as Clean Makassar (Makassar Tidak Rantasa-MTR) and Smart City (Kota Dunia) based on local wisdom using the tagline of Makassar Sombere. Innovative leadership should be loaded with innovation as the significant impact of sustainable transformation towards smart city with three main goals: to reconstruct the existing miserable community fate for the better future, to restore urban planning to be more convenient and livable, and lastly to reform leading bureaucracy to have globally recognized and standardized services. This in turn will be beneficial in fighting against corruptive practices and will be applicable in achieving international standard of public services as intended. The fundamental issues to overview are the real condition of Makassar city leadership in enhancing community welfare, the implementation of innovative leadership, and determinant factors of such leadership to be applied within the public policy of Makassar city government.